IMPLEMENTATION OF VISUAL METAPHOR-BASED MEDIA ON CELL MATERIAL TOWARD STUDENTS' CRITICAL THINKING SKILLS AND LEARNING MOTIVATION IN GRADE VIII OF SMP NEGERI 6 MAJALENGKA - Atih Novila Windiyani; Anna Fitri Hindriana; Agus Yadi Ismail (Indonesian Journal of Learning and Instruction, 2025)
Students' difficulties in understanding the abstract concept of cells, along with low learning motivation and critical thinking skills, prompted this study. The aim was to examine the implementation of metaphor-based visual learning media on cell material and its effects on the critical thinking skills and learning motivation of 8th-grade students at SMP Negeri 6 Majalengka. The study was conducted from February to April 2025 using a Research and Development (R&D) method with the ADDIE model. A sample of 52 eighthgrade students was selected through proportional random sampling. The media was developed in the form of a video titled "The Cell as a Unique School of Life", integrating everyday life analogies through visual metaphors. Data were collected through expert validation, student and teacher questionnaires, pre- and post-tests on critical thinking skills, and learning motivation questionnaires. Results showed that the media was highly valid (average score of 90.75%), practical to use (teacher response: 93.77%, student response: 87.54%), and significantly improved students’ critical thinking skills (mean rank of experimental group: 33.72; control group: 19.27). Learning motivation also increased, with extrinsic motivation at 92.30% and intrinsic motivation at 90.29%. Pearson correlation analysis indicated that the media had a stronger influence on learning motivation (r = 0.744) than on critical thinking skills (r = 0.609). Metaphor-based visual media effectively helps students understand abstract cell concepts, enhances critical thinking skills, and boosts learning motivation. This approach is recommended for science teachers as a meaningful, contextual learning strategy aligned with the Merdeka Curriculum.